Pronunciation Error of English Silent Letters by Unklab Nursing Students - Boy Lumoindong (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research was aimed at discovering the kinds of pronunciation errors made by the nursing students of Universitas Klabat in Pre Intermediate 1 class of 2025/2026 academic year. It is a descriptive quantitative method by involving 20 students from the total population of 40. Pronunciation test and interview were used as the research instruments. In this research, the researcher used 10 sentences for students to read. Every sentence has its specific English word with silent letter which became the target word to find out if the student could read them well. Every silent letter will only appear once in every sentence and the students were not allowed to repeat their pronunciations. The results of the research clearly showed that the students were preconditioned to make two kinds of errors, which are pre-systematic errors and systematic errors. The pre-systematic errors occurred more frequently than the other one. The highest errors made by the students were silent letters “l” (e.g. talk) and “p” (e.g. pneumonia) where numbers of errors for both letters were 30 (50%) out of 60 errors. The conclusion could be that the students faced difficulties when pronouncing words that are normally rare in use in their daily English practices and also because the students do not have good skills.